(untitled) - Jørgensen, Sven Erik (Southampton, 2009)
This textbook is ideal to be used alongside the Handbook of Ecological Modelling and Informatics (978-1-84564-207-5) for third year students to answer the question: how to go modelling? Jorgensen clearly details the basic knowledge of ecological modelling, with useful illustrations and examples. These give the user an excellent tool to understand what the various model types/network calculations can do and when to use which type as a tool to solve a specific problem.
Keywords: Ecology,Ecology,Ecology,Sinh thái học,Sinh thái học,Sinh thái học; Data processing,Databases,Computer simulation,Mô phỏng máy tính,Xử lý dữ liệu,Cơ sở dữ liệu